Adaptation of the sexual and reproductive empowerment scale for adolescents and young adults in Kenya. - Elizabeth K Harrington; Ouma Congo; Syovata Kimanthi; Annabell Dollah; Maricianah Onono; Nelly Mugo; Ruanne V Barnabas; Elizabeth A Bukusi; Ushma D Upadhyay (Public Library of Science (PLoS), 2023)
Measuring empowerment is critical to understanding the level of control adolescents and young adults (AYA) have over their sexual and reproductive health (SRH) behaviors, and could provide a key window into addressing their unique SRH needs. We adapted the Sexual and Reproductive Empowerment (SRE) scale for AYA for use in an East African context. This multi-method qualitative study sampled 15-23 year-old female adolescents and young adults in Kisumu, Kenya. We conducted in-depth interviews (n = 30) and analyzed transcripts with an inductive, constant comparison approach. Empowerment domains were integrated with Kabeer's (1999) framework in a conceptual model, which we referenced to revise the original and develop new scale items. Items underwent expert review, and were condensed and translated through team-based consensus-building. We evaluated content validity in cognitive interviews (n = 25), during which item phrasing and word choice were revised to generate an adapted SRE scale. Participants (n = 55) had a median age of 18 (range 16-23), and 75% were under 19 years. We categorize three types of adaptations to the SRE scale: new item generation, item revision, and translation/linguistic considerations. We developed nine new items reflecting AYA's experiences and new domains of empowerment that emerged from the data; new domains relate to self-efficacy in accessing sexual and reproductive health care, and how material needs are met. All items were revised and translated to echo concepts and language relevant to participants, navigating the multilingualism common in many African countries. Centering the voices of female Kenyan AYA, this study provides insight into measuring the latent construct of adolescent sexual and reproductive empowerment in an East African setting, and supports the adapted SRE scale's content validity for Kenya. We detail our multi-method, theory-driven approach, contributing to limited methods guidance for measure adaptation across contexts and among diverse adolescent populations.